THE STUDENTS’ NERVOUSNESS MODEL IN TEACHING LEARNING PROCESS - Amiruddin, Mohammad; Nazalatus S, Evha (The Ellite of Unira, 2024)
This study attempts to discover the models of students' anxiousness. This is a qualitative study conducted utilizing a descriptive case study. The study's participants are English Department students. Observation and interviews with students were performed to get information about the models and elements driving their worry. The study's findings show that pupils encounter two types of Nervousness models: interference and deficiency models. Interference models are more powerful than deficit models. Their English talents become the second determining element. Students seldom feel nervous when conversing with their classmates. When they are around their friends, they are able to communicate in English naturally and without concern.